France : Financial Sector Assessment Program-Detailed Assessments of Observance of Standards and Codes including Banking Supervision, Insurance Regulation, Securities Legislation, Monetary and Financial Policy Transparency, Payments Systems, Securities Settlement, and Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The Detailed Assessments of the Observance of Standards and Codes on France reviews compliance with Basel Core Principles for effective banking supervision. The French insurance market is notable for its broad range of distribution channels, which include tied agents, insurance brokers, salaried sales forces, direct writing mutuals, and financial institutions. France fulfills all prerequisites for effective payment clearing and settlement systems. Capital markets are large and sophisticated, with a range of equity, debt, derivative, and mutual fund products available to investors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet